KLASIFIKASI WARNA DALAM BAHASA MADURA DIALEK SUMENEP: ANALISIS BERLIN DAN KAY - Nurul Fadhilah; Hodairiyah Hodairiyah; Ema Wilianti Dewi (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2022)
The goal of this research is classifying the basic and non-basic colors of Sumenep Madurese dialect. This research is descriptive qualitative in which the data were analyzed using the universal color theory of Berlin and Kay (1969) and also an ethnolinguistic approach. As a result, the Sumenep Madurese dialect has six basic color names, namely potѐ 'white', celleng 'black', mѐra 'red', bhiru 'green', konѐng 'yellow', and cokklat 'brown', and also three color names classified in non-basic colors, namely bhiru 'biru', bungo 'purple', and bu-abu 'gray'. The color vocabularies in Sumenep Madurese dialect are in the form of lingual unit of word, such as the naming of basic colors because they are monolexemic, and lingual unit of phrase, such as derived colors from the basic or non-basic colors. The implicational hierarchy of basic colors in the Sumenep Madurese dialect is different from the implicational hierarchy of basic colors in Berlin and Kay's theory which was the result of 80 world language studies. The environment and the different habits of speech communities influence this difference. In brief, language as a cultural product affects the formation of the color lexicon.